Small intestinal NK/T-cell lymphoma with malignant peritoneal effusion as the first symptom: a case report and literature review - Zhou, Bing; Zhao, Qihan; Li, Xiaohua; Liu, Haoru; Hao, Hua (Frontiers in Medicine, 2025)
IntroductionSmall intestinal NK/T-cell lymphoma (NK/T-L) is a rare condition, and cases presenting with malignant peritoneal effusion as the initial symptoms are not well-documented. We report a unique case that contributes to the understanding of this rare disease.Case reportA 47-year-old man was admitted to the hospital with a chief complaint of abdominal distension and weight loss persisting for over 2 months. Imaging studies revealed ascites and localized thickening of the small intestine. Paracentesis cytology revealed a significant presence of small-to-medium-sized lymphoid cells. Immunohistochemistry confirmed a diagnosis of T-cell lymphoma. Histological examination confirmed primary NK/T-L of the small intestine after PET-CT excluded metastases from other sites. Despite aggressive chemotherapy, the patient’s condition deteriorated, resulting in his death 4 months later.DiscussionThis case highlights the importance of considering small intestinal NK/T-L in patients with abdominal symptoms and malignant peritoneal effusion. The aggressive nature and poor prognosis of this disease pose challenges in diagnosis and treatment. Increased awareness among clinicians and pathologists is crucial for early detection and improved patient outcomes.